The barrier and protective functions of intestinal mucin in defense against Candida albicans - Liu, Yuanyuan; Li, Dongmei; Ma, Li; Wen, Yiyang; Shi, Dongmei (Frontiers in Microbiology, 2025)
Candida albicans (C. albicans) is an opportunistic fungal pathogen that typically colonizes intestinal mucosal surfaces asymptomatically. However, dysbiosis or disruption of the mucosal barrier can trigger its overgrowth, leading to mucosal infections and, in severe cases, systemic disease. Intestinal mucins, the main components of mucus, play critical roles in host defense by suppressing filamentation-associated gene expression, blocking the yeast-to-hypha transition, and inhibiting key virulence traits including adhesion, biofilm formation, and secretion of hydrolytic enzymes. While their function as physical barriers is well established, the molecular mechanisms underlying mucin–fungus interactions remain incompletely understood. By targeting the virulence rather than the viability of C. albicans, mucins offer potential advantages over conventional antifungal therapies, including limiting drug resistance, improving biofilm penetration, and preserving mucosal homeostasis. This review highlights recent advances in understanding the biological and immunological roles of mucins in modulating C. albicans colonization and infection, and discusses their promise as novel therapeutic and diagnostic agents in intestinal candidiasis.